Remapping biblical studies CUREMP at thirty - Crowder, Stephanie Buckhanon 1969-; Foskett, Mary F. 1961- (Atlanta Society of Biblical Literature, 2023)
"This volume celebrates the thirty years of innovative scholarship and service supported by SBL's Committee on Underrepresented Racial and Ethnic Minorities in the Profession (CUREMP), a vital body in SBL dedicated to advancing the representation and work of racial and ethnic minoritized scholars in biblical studies. The volume includes the presidential addresses of groundbreaking scholars Brian K. Blount, Fernando F. Segovia, Vincent L. Wimbush, and Gale A. Yee with fifteen responses and reflections from members who have led and are leading the way for future generations of scholars"--
Description based on publisher supplied metadata and other sources
Keywords: Society of Biblical Literature -- Committee on Underrepresented Racial and Ethnic Minorities in the Profession; Bible -- Criticism, interpretation, etc -- History; Bible -- Study and teaching